2018
DOI: 10.1007/s12298-018-0627-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of genes associated with sucrose accumulation and its effect on source–sink relationship in high sucrose accumulating early maturing sugarcane variety

Abstract: Sucrose synthesis/accumulation in sugarcane depends on the source-sink communication wherein source responds to sink demand for photoassimilate supply. Sucrose in stalk (sink) acts as signal, and sends feedback to restrain further synthesis of sucrose by regulating photosynthetic efficiency of leaves (source). Hence sucrose synthesis/accumulation is controlled by many genes and regulatory sequences including 3 invertases (SAI, CWI, NI), sucrose synthase (SuSy) and sucrose phosphate synthase (SPS). SPS and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 50 publications
3
20
0
1
Order By: Relevance
“…As a C4 grass, sugarcane photosynthesis includes a pathway to obtain a four-carbon compound, a process that occurs in the mesophyll and is orchestrated by PEPC. In agreement with Verma and colleagues [40], we noted that high biomass genotypes may require a more intense expression of PEPC coding genes to support metabolic functions other than sucrose accumulation. Expression of PEPC genes was lower in young leaves associated with maturing culms but was practically invariable in leaves connected with more mature stalks [40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a C4 grass, sugarcane photosynthesis includes a pathway to obtain a four-carbon compound, a process that occurs in the mesophyll and is orchestrated by PEPC. In agreement with Verma and colleagues [40], we noted that high biomass genotypes may require a more intense expression of PEPC coding genes to support metabolic functions other than sucrose accumulation. Expression of PEPC genes was lower in young leaves associated with maturing culms but was practically invariable in leaves connected with more mature stalks [40].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with Verma and colleagues [40], we noted that high biomass genotypes may require a more intense expression of PEPC coding genes to support metabolic functions other than sucrose accumulation. Expression of PEPC genes was lower in young leaves associated with maturing culms but was practically invariable in leaves connected with more mature stalks [40]. In addition, a group of photophosphorylation genes coding for Psa, Psb and cytochrome proteins formed a downregulated cluster in low biomass genotypes (Figure 12 in Additional file 3).…”
Section: Discussionsupporting
confidence: 92%
“…However, CWINV overexpression can promote monomer accumulation in leaves, impairing carbohydrate storage and affecting growth, as described in cassava (42). SPS and CWINV have been shown to be highly expressed in sugarcane before maturation of culms, precisely to allow the development of leaves and to compensate for sucrose storage requirements in sink tissue (40). These authors also pointed out that genes coding for enzymes such as PEPC and SUT1 can show stable or increased expression levels in more mature leaves.…”
Section: Discussionmentioning
confidence: 92%
“…In agreement with Verma and colleagues (40), we noted that high biomass genotypes may require a more intense expression of PEPC coding genes to support metabolic functions other than sucrose accumulation. Expression of PEPC genes was lower in young leaves associated with maturing culms but was practically invariable in leaves connected with more mature stalks (40). In addition, a group of photophosphorylation genes coding for Psa, Psb and cytochrome proteins formed a downregulated cluster in low biomass genotypes (Figure 12 in Additional le 3).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the application of GA3 showed a positive impact on some stages of development leading to an increase in cane yield compared to untreated controls. Various research programs revealed that GA3 had an effect on the activity of sucrose phosphosynthase, one of the major enzymes involved in the synthesis of sucrose [7], and promoted the proliferation of sink tissues, leading to an improved assimilation process in sugarcane [8][9][10]; economic efficiency was thereby enhanced. In addition, GA3 increased abiotic stress tolerance in crops like sugarcane that are grown in, for example, salinated environments [11].…”
Section: Introductionmentioning
confidence: 99%